On the Temporal and Functional Origin of L2 Disadvantages in Speech Production: A Critical Review - Runnqvist, Elin; Strijkers, Kristof; Sadat, Jasmin; Costa, Albert (Frontiers in Psychology, 2011)
Despite a large amount of psycholinguistic research devoted to the issue of processing differences between a first and a second language, there is no consensus regarding the locus where these emerge or the mechanism behind them. The aim of this article is to briefly examine both the behavioral and neuroscientific evidence in order to critically assess three hypotheses that have been put forward in the literature to explain such differences: the weaker-links, executive control and post-lexical accounts. We conclude that (a) while all stages of processing are likely to be slowed down when speaking in an L2 compared to an L1, the differences seem to originate at a lexical stage; and (b) frequency of use seems to be the variable mainly responsible for these bilingual processing disadvantages.